The pleasures and sorrows of work. - De Botton, Alain, 1969- (London : Penguin, 2009)
We spend most of our waking lives at work - in occupations often chosen by our unthinking sixteen-year-old selves. And yet we rarely ask ourselves how we got there or what it might mean for us. Equally intrigued by work's pleasures and its pains, Alain de Botton here heads out into the under-charted worlds of the office, the factory, the fishing fleet and the logistics centre, ears and eyes open to the beauty, interest and sheer strangeness of the modern workplace. Along the way he tries to answer some of the most urgent questions we can ask about work: Why do we do it? What makes it pleasurable? What is its meaning? And why do we daily exhaust not only ourselves but also the planet?
Keywords: Arbeid; Arbeidsethos